Pengembangan Bahan Ajar Digital E-Book Asik Nian Pada Pembelajaran IPAS Kelas IV SD - Henny Risnawaty Putri; M Taheri Akhbar; Susanti Faipri Selegi (STKIP Andi Matappa Pangkep, 2024)
This study aims to produce valid, practical, and effective digital e-book teaching materials on Indonesian Cultural Diversity in science and social studies learning for grade IV elementary school. This study uses the research and development method using the ADDIE model (analyze, design, development, implementation, evaluation). The results of the data analysis shows that the developed e-book is included in the